The oncogenic Golgi phosphoprotein 3 like overexpression is associated with cisplatin resistance in ovarian carcinoma and activating the NF-κB signaling pathway - He, Shanyang; Niu, Gang; Shang, Jianhong; Deng, Yalan; Wan, Zhiyong; Zhang, Cai; You, Zeshan; Shen, Hongwei (Journal of experimental & clinical cancer research, 2017)
Chemo-resistance is a leading cause of tumor relapse and treatment failure in patients with ovarian cancer. The identification of effective strategies to overcome drug resistance will have a significant clinical impact on the disease. The protein and mRNA expression of GOLPH3L in ovarian cancer cell lines and patient tissues were determined using Real-time PCR and Western blot, respectively. 177 human ovarian cancer tissue samples were analyzed by IHC to investigate the association between GOLPH3L expression and the clinicopathological characteristics of ovarian cancer patients. Functional assays, such as MTT, FACS, and Tunel assay used to determine the oncogenic role of GOLPH3L in human ovarian cancer progression. Furthermore, western blotting and luciferase assay were used to determine the mechanism of GOLPH3L promotes chemoresistance in ovarian cancer cells. The expression of GOLPH3L was markedly upregulated in ovarian cancer cell lines and tissues, and high GOLPH3L expression was associated with an aggressive phenotype and poor prognosis with ovarian cancer patients. GOLPH3L overexpression confers CDDP resistance on ovarian cancer cells; however, inhibition of GOLPH3L sensitized ovarian cancer cell lines to CDDP cytotoxicity both in vitro and in vivo. Additionally, GOLPH3L upregulated the levels of nuclear p65 and phosphorylated inhibitor of nuclear factor Kappa-B kinase-β and IκBα, thereby activating canonical nuclear factor-κB (NF-κB) signaling. Our findings suggest that GOLPH3L is a potential therapeutic target for the treatment of ovarian cancer: targeting GOLPH3L signaling may represent a promising strategy to enhance platinum response in patients with chemoresistant ovarian cancer.